Sex-related differences in effect-site concentration of remifentanil for preventing anesthetic emergence cough in elderly patients - Lee SY (Dove Medical Press, 2018)
Sook Young Lee, Yun Yong Jeong, Byung Ho Lee, Ji Eun Kim Department of Anesthesiology and Pain Medicine, Ajou University School of Medicine, Suwon, Republic of Korea Purpose: Cough on anesthetic emergence should be prevented considering its dangerous complications. Target-controlled infusion (TCI) of remifentanil can reduce emergence cough effectively, and sex-related differences in effect-site concentration (Ce) of remifentanil have been evaluated in young patients. In this study, we determined the Ce of remifentanil for preventing emergence cough following extubation in male and female elderly patients and evaluated the sex-related difference.Patients and methods: Twenty-three male and 22 female elderly patients aged between 60 and 75 years were enrolled. Anesthesia was maintained with sevoflurane and remifentanil TCI. The Ce of remifentanil for preventing emergence cough was determined for each sex using isotonic regression method with a bootstrapping approach, following Dixon’s up-and-down method.Results: The Ce of remifentanil for preventing emergence cough in 50% (EC50) and 95% (EC95) of the population was significantly lower in females than in males. Isotonic regression revealed the EC50 (83% confidence interval [CI]) of remifentanil was 1.67 (1.55–1.83) ng/mL in females and 2.60 (2.29–2.91) ng/mL in males. The EC95 (95% CI) of remifentanil was 2.30 (2.02–2.62) ng/mL in females and 3.41 (3.27–3.58) ng/mL in males. Dixon’s up-and-down method indicated that the mean EC50 in females was lower than in males (1.56±0.26 ng/mL vs 2.56±0.37 ng/mL, P<0.001).Conclusion: The remifentanil requirement for preventing emergence cough was lower in female than in male elderly patients, indicative of sex-related differences in Ce of remifentanil. Sex should be considered when using remifentanil TCI for preventing emergence cough in elderly patients. Keywords: effect-site concentration, elderly patients, emergence cough, remifentanil, sex difference